Standardisation of functional baked products utilising under exploited tubers - Rekha Anaveri (Department of Home Science, College of Horticulture, 2016)
The present study entitled “Standardisation of functional baked products utilising under exploited tubers” was proposed to standardise the preparation of low calorie, trans fat free buns and cookies incorporating elephant foot yam and tannia flour and to enrich the products with functional ingredients. The study also evaluated the physical, biochemical and nutritional qualities, organoleptic and keeping qualities of the developed products during storage. The study was carried out in three experiments. Tuber based buns (BYT1 to BYT5 and BTT6 to BTT10) and cookies (CYT1 to CYT5 and CTT6 to CTT10) were standardised in eleven treatments including control (BT0 and CT0: refined wheat flour). Soyabean oil was used as fat substitute for the standardisation of tuber flour based products. Sucralose and sorbitol were used as sugar substitutes in buns and cookies respectively. The highest mean score for different organoleptic attributes was noticed for buns and cookies prepared using 20 per cent EFY/tannia flour with 80 per cent wheat flour. Hence, BYT5, BTT10, CYT5 and CTT10 were selected for the preparation of enriched products. The selected tuber flour based buns and cookies were enriched with functional ingredients such as wheat bran (WB), garden cress seed (GS) and flax seed (FS). Fourteen treatments were undertaken for the standardisation of enriched tuber flour based buns and cookies separately, including the control. Based on organoleptic scores, tuber flour based buns enriched with 2 per cent WB and 2 per cent GS and FS in 1:1 proportion (EBYT1 and EBTT7) and cookies enriched with 2 per cent WB and 6 per cent GS and FS in 1:1 proportion (ECYT15 and ECTT21) were selected for the quality evaluation during storage. The enriched tuber flour based buns and cookies were packed in polyethylene and laminated aluminium pouches respectively for storage. The buns were stored for five days and cookies for forty days and evaluated for physical, biochemical and nutritional, organoleptic and shelf life qualities. Compared to control, better loaf weight and lower loaf volume was noticed for enriched buns. The crust colour was darker for enriched buns and cookies. During storage, an increase in the weight of cookies was noticed whereas the diameter, thickness and spread factor remained same. The hardness of cookies reduced during storage due to 2 to 4 per cent increase in moisture content. The highest carbohydrate content was noticed in tannia flour based enriched buns (59.64%) and cookies (53.64%), which decreased in all the products during storage. Significant variation in protein, fat, fibre and total ash content of the products was noticed and the content of these nutrients reduced significantly during storage. The free fatty acid content was not noticed in enriched bun, but in cookies, it was noticed at the end of storage. The calcium, iron, sodium and potassium content of the enriched tuber based buns and cookies were higher, compared to control. A reduction in mineral content was noticed in all the products during storage. The total flavonoid content of enriched buns and cookies varied from 85.48 to 89.56 mg 100g-1 and 78.59 to 84.39 mg 100g-1 respectively. Maximum total phenol content and antioxidant activity was noticed in enriched tannia flour based buns (121.6 mg 100g-1; 26.14%) and cookies (111.5 mg 100g-1; 27.44%). The total flavonoids, phenol and antioxidant activity decreased significantly during storage of the products. Peroxides were not detected in products during storage and iodine value of the enriched buns and cookies ranged from 89.23 to 97.34 and 113.24 to 115.54 respectively and it decreased significantly during storage of the products. The mean score for the overall acceptability of enriched buns was above 7.00 and slight reduction in mean score was noticed in 5 days of storage. Overall acceptability scores for the enriched tuber based cookies improved in forty days of storage. Maximum mean score for overall acceptability was noticed in tannia flour based enriched buns and cookies. The enriched tuber flour based products had lower glycemic load, glycemic index and gross energy value than control buns and cookies. Bacterial load was noticed in enriched buns from 3rd day onwards and in cookies it was noticed initially and the load increased in all the products with advancement in days of storage. Fungal count was noticed towards the end of storage and yeast count was not detected during storage. The total microbial count was found to be within the permissible limit suggested for such products. The cost of production for enriched buns (Rs. 18.24/100g) and cookies (Rs. 26.99/100g) was higher than the refined wheat flour based buns and cookies.